Pregabalin potentiates the analgesic effect of tramadol, diclofenac and paracetamol in chicks: Isobolographic analysis - Qutaiba M. Mohammed; Yasser M. Albadrany (Iraqi Journal of Veterinary Sciences, 2022)
The study aimed to reveal pregabalin’s median effective analgesic dose (ED50) and determine the type of analgesic interaction with tramadol, diclofenac, and paracetamol in chicks. The electrical stimulator device was used to detect pain before and after treatment, and through ascending and descending in doses and depending on the up and down method, the median effective analgesic doses were determined for all drugs used in the study, and then the interaction experiment was conducted at a fixed ratio 0.5:0.5 of pregabalin with each of tramadol, diclofenac and paracetamol of their individual ED50 values, the results were subjected to the isobolographic analysis to determine the type of interaction. Results showed that ED50s for pregabalin, tramadol, diclofenac, and paracetamol in chicks were 156.5, 0.82, 5.65, and 10.74 mg/kg, respectively. Concomitant administration of drugs pregabalin: tramadol, pregabalin: diclofenac and pregabalin: paracetamol at a fixed ratio 0.5:0.5 of their individual ED50 values reduced their ED50s to 36.2:0.18, 64.3:2.3 and 64.3:4.3 mg/kg respectively. Isobolographic analysis showed synergistic analgesic effects of both drugs interaction. The calculated interaction indexes were 0.45, 0.81, and 0.81, respectively. We conclude from the outcomes that the analgesic interaction was synergistic between pregabalin and tramadol significantly, while the analgesic interaction of pregabalin with both diclofenac and paracetamol was also synergistic, but to a lesser extent.